X-Ray Crystallographic Studies of Mononuclear and Binuclear Copper(II) Complexes with Some Schiff-bases - Dodwad, S.S.; Salvi, S.V.; Dhamnaskar, R.S. (Asian Journal of Chemistry, 2010)
Some mononuclear and binuclear copper(II) complexes with Schiff bases have been synthesised and characterised. They have a general formula [CuL2] and [(CuL)2Cl2] where L = C17H12NOX and X = H, CH3, OCH3, C6H5 and Cl. The present investigation reports the crystal structure studies done by X -ray powder method. The observed reflection are indexed. All observed reflections indicate single phase for every complex. Lattice constants are determined within an accuracy of 0.01 Å. All the mononuclear complexes are tetragonal while binuclear complexes have orthorhombic geometry.